Classes of Frequencies Free of Mutual Interference: Elements of a Theory of Frequency Assignments - Castellini, Nello R. (IEEE transactions on electromagnetic compatibility, 1964)
The mutual interference chart (MIC) gives the compatibility that exists between the channels of a radio set. This property of the chart is used to determine classes of frequencies that are compatible (in the sense of freedom from mutual interference) with given transmitting or receiving frequencies. The approach is based on the elementary theory of classes. It is shown that from the chart two categories of fundamental classes can be defined: those classes that contain undesired frequencies giving rise to interference in the presence of a given desired frequency and those classes that contain desired frequencies which in the presence of a given undesired frequency are subject to interference. The classes of compatible frequencies resulting from these definitions are determined for simple circuits containing one or more duplex channel terminals in various configurations. A set of classes characterizes each circuit; if the set is solved, it leads to classes of interference free frequencies for it. Some results obtained in the extension of the theory to more complex circuits are briefly mentioned. The logical extension of the results, surprisingly, lead to a relative simple solution of the problem of assignment.